PERAN PENDIDIK DALAM MENANAMKAN NILAI-NILAI KEJUJURAN MELALUI PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN (PKn) PADA PESERTA DIDIK DI SEKOLAH DASAR - Sudarmin Sudarmin; Muhajir Muhajir; Dideng Kadir (Universitas Pakuan, 2021)
THE ROLE OF EDUCATORS IN INSTILLING THE VALUES OF HONESTY THROUGH CITIZENSHIP EDUCATION LEARNING IN ELEMENTARY SCHOOL STUDENTSThis study aims to describe the role of educators in instilling honesty values through Citizenship Education (Civics) learning to students and to explain the efforts of educators in instilling honesty values in students. This type of research is qualitative with the phenomenon of analysis and the meaning contained in the values of honesty. The data were collected through interviews, observation and documentation, then the data were analyzed with several steps of use, categorization, data intervention, then the data was validated by adding time and tringulation. The results showed that there were changes in attitudes and behavior, students did not cheat during tests on the site, returned library books on time, were able to honestly state the reasons when they came to school, were honest when studying in the canteen, became knowledgeable people. , disciplined, and sportsmanship.